2015
DOI: 10.1177/0300060515581670
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cuff pressure and position of cylindrical-cuff and tapered-cuff tracheal tubes during laparoscopic abdominal surgery

Abstract: Objectives: To evaluate changes in cuff pressure and position of tapered-cuff and cylindrical-cuff tracheal tubes (TTs) during laparoscopic cholecystectomy; to compare the frequency of endobronchial intubation and airway complaints with the two types of TT. Methods: Patients were randomly assigned to intubation with a TT with a cylindrical cuff (group C) or a tapered cuff (group T). Anaesthesia was maintained with sevoflurane, O 2 and N 2 O after intubation. TT cuffs were inflated to 20 cm H 2 O; changes in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, no data are available on the safety or the cost-effectiveness of tapered-cuff tracheal tubes. Shin et al 57 showed that in anesthetized subjects receiving N 2 O, P cuff was significantly lower in subjects with tapered-cuff compared with those with standard-cuff tracheal tubes. However, the number of included subjects was small, P cuff was not continuously measured, and clinical signs of tracheal lesions were similar in the 2 groups.…”
Section: Tapered-cuff Tracheal Tubesmentioning
confidence: 99%
“…To our knowledge, no data are available on the safety or the cost-effectiveness of tapered-cuff tracheal tubes. Shin et al 57 showed that in anesthetized subjects receiving N 2 O, P cuff was significantly lower in subjects with tapered-cuff compared with those with standard-cuff tracheal tubes. However, the number of included subjects was small, P cuff was not continuously measured, and clinical signs of tracheal lesions were similar in the 2 groups.…”
Section: Tapered-cuff Tracheal Tubesmentioning
confidence: 99%
“…Supplementary Table 2 shows the intraoperative cuff pressures. The median (IQR) cuff pressures (mm Hg) were significantly lower for the tapered cuff than for the control cuff after tracheal intubation [9 (7-12) vs. 11 (8)(9)(10)(11)(12)(13)(14); P = 0.009)], after neck extension [9 (7-12) vs. 12 (10-15); P < 0.001] and after retraction [18 (15-23) vs. 25 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31); P = 0.007, Figure 3A]. Pressure differentials (i.e., pre-post change) caused by surgical retraction and pressure adjustment were smaller in the tapered group than in the control group (Figure 3D).…”
Section: Intraoperative Cuff Pressure and The Need For Pressure Adjus...mentioning
confidence: 99%
“…Fluid or air leak was less around a tapered cuff than around a conventional cylindrical high-volume low-pressure cuff ( 11 , 12 ). Tapered cuffs also achieve a better air seal with reduced cuff pressure ( 13 ), thereby leading to a smaller change in cuff pressure during compressive forces such as pneumoperitoneum in laparoscopic surgery ( 14 ). There is evidence suggesting tapered cuffs reduce the incidence of postoperative sore throat and dysphonia ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…ETT cuff pressure is affected by environmental circumstances/factors and therapeutic interventions/factors (Khalil et al, 2019). These factors are body positions (Lizy et al, 2011; Athiraman et al, 2015), peak inspiratory pressure (PIP) (Chenelle et al, 2015), core body temperature (Lizy et al, 2011; Erolçay et al, 2002), blood pressure, the opening of the sternum and pleura (Erolçay et al, 2002), nitrous oxide use (Shin et al, 2015), ventilator pressures, tracheal aspiration (Lizy et al, 2011) and agitation (Sole et al, 2009). These factors cause a decrease or increase in the cuff volume, resulting in a deviation from its normal value.…”
Section: Introductionmentioning
confidence: 99%